1977
DOI: 10.1002/j.1879-3479.1977.tb00641.x
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Epignathus—Clinical, Radiologic, and Pathologic Considerations

Abstract: In retrospect, a diagram could hace been made from the antenatal radiological examination of the case of epignathus presented here. The features of the epignathus are considered with respect to antenatal diagnosis and subsequent reparative surgery. Specific features such as axial organization, maturity of all tissues, and identical ossification points between host and parasite-all of which are evident in this case-favor the malformative origin of epignathi, thus distinguishing them from teratomata.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 4 publications
(3 reference statements)
0
10
0
1
Order By: Relevance
“…Epignathus are intraoral malformations present at birth and the point of origin, specifically the alveolar bone or jaw (Nogales et al, 1977;Zakaria, 1986;Maeda et al, 1989;Izadi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Epignathus are intraoral malformations present at birth and the point of origin, specifically the alveolar bone or jaw (Nogales et al, 1977;Zakaria, 1986;Maeda et al, 1989;Izadi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Labour may be complicated by dysfunctional uterine activity [1]. Postpartum, pharyngeal teratomas may present as a mass extruding from the mouth or nares, and be associated with respiratory distress or asphyxia (6], this being more common with the larger pharyngeal tumours or epignathi [7][8][9]. Most tumours are, however, pedunculated, causing much less severe respiratory obstruction (I, 5, 10].…”
Section: Discussionmentioning
confidence: 99%
“…According to Levine et al (1990), the incidence of epignathus tumor is between 1 in 35,000 and 1 in 200,000 live births [14]. Nogales et al (1977) reported a single case of epignathus tumor in 800,000 deliveries in east Andalusia [7]. These lesions are not familial in nature.…”
Section: Oropharyngeal Teratomasmentioning
confidence: 91%
“…Ahfeld first proposed the twin theory in the late 1800's [6][7][8]. Schwalbe later suggested that teratomas arise, during embryogenesis, from displaced germ cells during migration to the genital ridge.…”
Section: Etiopathogenesismentioning
confidence: 99%